The Influence of Organizational Support, Motivation, and Completeness of ERM SOP on Compliance of Health and Medical Personnel - Mundakir Mundakir; Diny Wulansari (International Journal of Health and Social Behavior, 2025)
Compliance of healthcare and medical personnel with established procedures—particularly Enterprise Risk Management (ERM) Standard Operating Procedures (SOPs)—is crucial for ensuring patient safety, high-quality healthcare services, and the sustainable operation of hospitals. This study analyzes the influence of Organizational Support, Motivation, and the Completeness of ERM SOPs on personnel compliance at Petrokimia Gresik Driyorejo Hospital. A quantitative approach using a survey method was employed. The study population included all healthcare and medical personnel directly involved with ERM SOPs. Through purposive sampling, 85 respondents were selected. Data collection used closed-ended questionnaires tested for validity and reliability. Data were analyzed using multiple linear regression through SPSS version 25. The analysis found that Organizational Support (X1), Motivation (X2), and ERM SOP Completeness (X3) simultaneously had a statistically significant effect on Compliance (Y), with the F-test showing F_calculated > F_table and significance < 0.05. Individually, all three independent variables showed a positive and significant relationship with compliance. Among them, ERM SOP Completeness had the greatest influence, followed by Motivation and then Organizational Support. These findings emphasize that clear, comprehensive, and accessible SOPs are essential in guiding staff behavior and ensuring consistent adherence to risk management protocols. Additionally, motivated employees supported by the organization are more likely to comply with procedures and internal policies. Therefore, organizational strategies should not only focus on developing complete SOPs but also on fostering a supportive work culture and enhancing staff motivation through training, recognition, and leadership support. In conclusion, the study suggests that hospitals aiming to improve compliance with ERM procedures should adopt a holistic approach by investing in SOP development, providing consistent organizational support, and maintaining high levels of employee motivation. These efforts will contribute to better risk mitigation, service quality, and overall hospital performance.